The Effect of Financial Literacy and Entrepreneurship Education on Students’ Intentions to Pursue Entrepreneurial Careers - Binod Ghimire; Rewan Kumar Dahal; Surendra Prasad Joshi (Pravaha, 2023)
The present study examines the influence of entrepreneurship education (EE) and financial literacy (FL) on the ambitions of students to engage in entrepreneurial careers. The study used a quantitative research methodology to explore the interplay and impacts of these variables on the entrepreneurial career aspirations of students. An analysis was conducted using descriptive and inferential statistical methods based on primary data from a structured survey questionnaire administered to students from different university programs. Examining the study hypotheses indicates that students' ambitions to enter entrepreneurial careers are enhanced by their participation in entrepreneurship education programs and their comprehensive understanding of financial literacy. The study results substantially influence the acquisition of crucial financial management skills and the improvement of preparedness for entrepreneurial pursuits among students. Moreover, the study's enduring impacts on integrating EE and FL on entrepreneurial success offer significant insights for enhancing educational approaches.